Date palm biotechnology - Jain, Shri Mohan; Al-Khayri, Jameel M.; Johnson, Dennis V.; SpringerLink (Online service). (Dordrecht, Netherlands Springer Netherlands, 2011)
This important reference book is the first comprehensive resource worldwide that reflects research achievements in date palm biotechnology, documenting research events during the last four decades, current status, and future outlook.  It brings together the principles and practices of contemporary date palm biotechnology. The book is essential for researchers, policy makers, and commercial entrepreneurs concerned with date palm. It is invaluable for date palm biotechnology students and specialists. This monumental work is written by an international team of experienced researchers from both academia and industry.  Each chapter contains background knowledge related to the topic, followed by a comprehensive literature review of research methodology and results including the authors' own experience and supported with illustrative tables and photographs. In addition to an introductory chapter, the book consists of thirty two review chapters highlighting progress and current research status covering various aspects of date palm biotechnology in five sections: A) Discuss the research development, methodology, and commercial application of micropropagation  in seven chapters, B) Deal with the research development and applications of somaclonal variation and mutation in date palm, covered in seven chapters, C) Describe the status of date palm germplasm and current techniques employed in conservation and molecular characterization are described in seven chapters, D) Address research progress made in date palm genetics and breeding in eight chapters, E) Describe up-to-date progress made in metabolites and industrial biotechnology in three chapters.
Preface -- Introduction -- Section A: Micropropagation -- 1. Potential of date palm micropropagation for improving small farming systems -- 2. Date palm tissue culture: a pathway to rural development -- 3. Date palm micropropagation via somatic embryogenesis -- 4. Date palm micropropagation via organogenesis -- 5. Micropropagation of date palm using inflorescence explants -- 6. Bioreactors and automation in date palm micropropagation -- 7. Commercial date palm tissue culture procedures and facility establishment -- Section B: Somaclonal Variation, Mutation and Selection -- 8. Somaclonal variation in date palm -- 9. Growth abnormalities associated with micropropagation of date palm -- 10. Molecular detection of somaclonal variation in date palms -- 11. In vitro¬ selection for abiotic stress in date palm -- 12. Fusarium oxysporum f. sp. albedinis toxins utilization in selecting Bayoud-resistant date palm -- 13. Radiation induced mutations for date palm improvement -- 14. Magnetic field induced biochemical and growth changes in date palm seedlings -- Section C: Germplasm Biodiversity and Conservation -- 15. Date palm germplasm -- 16. In vitro conservation of date palm germplasm -- 17. Molecular markers in date palm -- 18. Biodiversity in date palm: molecular markers as indicators -- 19. Polymorphism and genetic relationship in date palm using molecular markers -- 20. Date palm genome project at the kingdom of Saudi Arabia -- 21. Potential of arbuscular mycorrhizal technology in date palm production -- Section D: Genetics and Genetic Improvement -- 22. Date palm genetics and breeding -- 23. Development of new Moroccan selected date palm varieties resistant to Bayoud -- 24. Molecular markers for Bayoud disease resistance in date palm -- 25. Towards sex determination of date palm -- 26. Interspecific hybridization and embryo rescue in date palm -- 27. In vitro flowering of date palm -- 28. Date palm cell and protoplast culture -- 29. Transgenic date palm -- Section E: Metabolites and Industrial Biotechnology -- 30. Secondary metabolites of date palm -- 31. Industrial biotechnology: date palm fruit applications -- 32. Date palm as a source of bioethanol producing microorganisms -- Index.
Electronic reproduction.
Keywords: Date palm -- Biotechnology; Electronic books